2021
DOI: 10.1111/ajco.13686
|View full text |Cite
|
Sign up to set email alerts
|

Differences in lesion interpretation between radiologists in two countries: Lessons from a digital breast tomosynthesis training test set

Abstract: Introduction In many western countries, there is good evidence documenting the performance of radiologists reading digital breast tomosynthesis (DBT) images. However, the diagnostic efficiency of Chinese radiologists using DBT, particularly type of errors being made and type of cancers being missed, is understudied. This study aims to investigate the pattern of diagnostic errors across different lesion types produced by Chinese radiologists diagnosing from DBT images. Australian radiologists will be used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…DBT could remove the overlapping of breast tissues on breast abnormalities, 37 and this can potentially equalize sensitivity for breast cancer detection in high and low dense breasts. In regard to lesion types, Shanghai radiologists demonstrated a lower sensitivity compared with Australian radiologists in detecting non-mass lesions (e.g., calcifications, architectural distortion, and asymmetric density), which is to some extent aligned with our previous study 38 . In the previous work, our team examined the performance in a high breast density test set of radiologists in Hong Kong who had a different medical education and radiology reading/interpretation systems from those in mainland China; therefore its result may not be generalized to radiologists from mainland China (such as Shanghai in this study).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…DBT could remove the overlapping of breast tissues on breast abnormalities, 37 and this can potentially equalize sensitivity for breast cancer detection in high and low dense breasts. In regard to lesion types, Shanghai radiologists demonstrated a lower sensitivity compared with Australian radiologists in detecting non-mass lesions (e.g., calcifications, architectural distortion, and asymmetric density), which is to some extent aligned with our previous study 38 . In the previous work, our team examined the performance in a high breast density test set of radiologists in Hong Kong who had a different medical education and radiology reading/interpretation systems from those in mainland China; therefore its result may not be generalized to radiologists from mainland China (such as Shanghai in this study).…”
Section: Discussionsupporting
confidence: 88%
“…In regard to lesion types, Shanghai radiologists demonstrated a lower sensitivity compared with Australian radiologists in detecting non-mass lesions (e.g., calcifications, architectural distortion, and asymmetric density), which is to some extent aligned with our previous study. 38 In the previous work, our team examined the performance in a high breast density test set of radiologists in Hong Kong who had a different medical education and radiology reading/interpretation systems from those in mainland China; therefore its result may not be generalized to radiologists from mainland China (such as Shanghai in this study). Shanghai readers were further found to perform better in detecting large lesions (versus small lesions) compared with Australian readers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may not necessarily be the volume of reading mammograms which impacts performance, but rather the type of cancer appearances they have been exposed to. A previous study identified that stellate masses and architectural distortion were the cancer appearances that Chinese radiologists found significantly more difficult to identify compared to Australian radiologists [22].…”
Section: Reading Volume and Experiencementioning
confidence: 94%
“…This difference was not only reported in digital mammogram test sets but also found in DBT test sets. For example, in a recent study, it was found that the false positive and false negative rates of Chinese radiologists reading the DBT test set via the BEAST platform was 52% and 69% compared with 36% and 35% in Australian radiologists ( 77 ). This large difference in cancer detection accuracy might imply that a great number of cancer cases could be missed or incorrectly reported in the clinical practices among MIC and LIC countries, which could have harmful implications for treatment outcomes of patients.…”
Section: Breast Screening Reader Training Programs and Breastmentioning
confidence: 99%
“…In addition, BREAST studies reported findings based on performances of radiologists from different countries in reading mammograms with different level of breast density and the ability to detect various types of cancer appearances. The most challenging type of cancer lesions to detect on mammograms for LIC radiologists were small lesions such as stellate/spiculated masses along with architectural distortions (the missed rate was 55%-75%) ( 77 , 78 ), while discrete masses and asymmetric density (or non-specific density) were more likely to be missed (31%-37%) or rated as equivocal (47%-50%) by HIC radiologists ( 77 , 79 ). This is in line with findings from the PERFORMS program where well-defined masses and asymmetric density accounted for the highest percentage of incorrectly diagnosed cases (25%) among UK radiologists ( 70 ).…”
Section: Breast Screening Reader Training Programs and Breastmentioning
confidence: 99%